GEOCHEMICAL CHARACTERISTICS OF DORO API TOI AND DORO API BOU, TAMBORA CALDERA, DOMPU AND BIMA DISTRICTS, WEST NUSA TENGGARA PROVINCE - Wahyu Ramadhan, Adam
The study was carried out on the Doro Api Toi and Doro Api Bou lava domes in the Tambora Caldera area, Dompu and Bima Regencies, West Nusa Tenggara. The lava dome is one of the products formed after the eruption of Mount Tambora in 1815. The research aims to determine the process of rock formation, magma series, and tectonic order with petrogenesis The method used in this research is petrographic analysis from thin section description, and rock geochemical analysis based on XRF (X-Ray Flourence Spectometry) and ICP-MS (Inductively Coupled-Plasma Mass Spectrometry) data in the form of percent weight percentages of major elements and trace element concentrations. Petrographic analysis of samples of Doro Api Toi and Doro Api Bou showed pyroxene andesit with porphyritic, vitriolic, flow, glomeroporphyritic with phenocryst plagioclase, pyroxene, opaque minerals, olivine, xenoliths tuff glass in the base mass of volcanic glass and plagioclase microlites. magma series samples showing the calc-alkali magma series and magmatism controlled by crystal fractionation and assimilation. Tectonic setting analysis show plate boundary tectonic environments in subduction areas that form volcanic features as island arcs which affected by arc contamination